Unraveling Anaerobic Metabolisms in a Hypersaline Sediment - Solchaga, Juan Ignacio; Busalmen, Juan Pablo; Nercessian, Débora (Frontiers in Microbiology, 2022)
The knowledge on the microbial diversity inhabiting hypersaline sediments is still limited. In particular, existing data about anaerobic hypersaline archaea and bacteria are scarce and refer to a limited number of genera. The approach to obtain existing information has been almost exclusively attempting to grow every organism in axenic culture on the selected electron acceptor with a variety of electron donors. Here, a different approach has been used to interrogate the microbial community of submerged hypersaline sediment of Salitral Negro, Argentina, aiming at enriching consortia performing anaerobic respiration of different electron acceptor compounds, in which ecological associations can maximize the possibilities of successful growth. Growth of consortia was demonstrated on all offered electron acceptors, including fumarate, nitrate, sulfate, thiosulfate, dimethyl sulfoxide, and a polarized electrode. Halorubrum and Haloarcula representatives are here shown for the first time growing on lactate, using fumarate or a polarized electrode as the electron acceptor; in addition, they are shown also growing in sulfate-reducing consortia. Halorubrum representatives are for the first time shown to be growing in nitrate-reducing consortia, probably thanks to reduction of N2O produced by other consortium members. Fumarate respiration is indeed shown for the first time supporting growth of Halanaeroarchaeum and Halorhabdus belonging to the archaea, as well as growth of Halanaerobium, Halanaerobaculum, Sporohalobacter, and Acetohalobium belonging to the bacteria. Finally, evidence is presented suggesting growth of nanohaloarchaea in anaerobic conditions.